(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In our example, we used the drug Fargals for the treatment of wounds in patients with phlegmon of the maxillofacial region of various etiologies. We proved that the developed treatment technology has a pronounced positive effect on the dynamics of microbial contamination and allows reaching a significant etiological titer of pathogenic microorganisms in the focus in 100% of patients by 3 days.